TIPE Regulates DcR3 Expression and Function by Activating the PI3K/AKT Signaling Pathway in CRC - Zhong, Mengya; Qiu, Xingfeng; Liu, Yu; Yang, Yan; Gu, Lei; Wang, Chenxi; Chen, Huiyu; Liu, Zhongchen; Miao, Jiayin; Zhuang, Guohong (Frontiers in Oncology, 2021)
Tumor necrosis factor-induced protein-8 (TIPE) is highly expressed in colorectal cancer (CRC). Decoy receptor 3 (DcR3) is a soluble secreted protein that can antagonize Fas ligand (FasL)-induced apoptosis and promote tumorigenesis. It remains unclear whether TIPE can regulate DcR3 expression. In this study, we examined this question by analyzing the relationship between these factors in CRC. Bioinformatics and tissue microarrays were used to determine the expression of TIPE and DcR3 and their correlation in CRC. The expression of TIPE and DcR3 in colon cancer cells was detected. Plasma samples were collected from CRC patients, and DcR3 secretion was measured. Then, dual-luciferase reporter gene analysis was performed to assess the interaction between TIPE and DcR3. We exogenously altered TIPE expression and analyzed its function and influence on DcR3 secretion. Lipopolysaccharide (LPS) was used to stimulate TIPE-overexpressing HCT116 cells, and alterations in signaling pathways were detected. Additionally, inhibitors were used to confirm molecular mechanisms. We found that TIPE and DcR3 were highly expressed in CRC patients and that their expression levels were positively correlated. DcR3 was highly expressed in the plasma of cancer patients. We confirmed that TIPE and DcR3 were highly expressed in HCT116 cells. TIPE overexpression enhanced the transcriptional activity of the DcR3 promoter. TIPE activated the PI3K/AKT signaling pathway to regulate the expression of DcR3, thereby promoting cell proliferation and migration and inhibiting apoptosis. In summary, TIPE and DcR3 are highly expressed in CRC, and both proteins are associated with poor prognosis. TIPE regulates DcR3 expression by activating the PI3K/AKT signaling pathway in CRC, thus promoting cell proliferation and migration and inhibiting apoptosis. These findings may have clinical significance and promise for applications in the treatment or prognostication of CRC.